Examination of satisfaction levels of visually impaired athletes - Çankaya, Cemali (2021)
This study was conducted to determine the effect of demographics on athlete satisfaction of visually impaired athletes. The visually impaired clubs had a total of 108 visually impaired athletes, including 43 men and 65 women, consisting of different visually impaired athletes. The basis of volunteerism was taken into consideration in the participation. Athlete satisfaction of visually impaired athletes was analyzed according to gender, disability status, Sports branches, how long they played sports, year of working with the coach and their degree of vision. The ‘athlete satisfaction scale’ developed by Türksoy (2008) was used as a data collection tool in the research. Results show that there is no significant difference in athlete satisfaction of visually impaired individuals(p>0.05) according to gender, disability status, how many years they have played sports, the year they work with the coach and the sport branch (p < 0.05).